2019
DOI: 10.1016/j.btre.2018.e00299
|View full text |Cite
|
Sign up to set email alerts
|

Xylan deterioration approach: Purification and catalytic behavior optimization of a novel β-1,4-d-xylanohydrolase from Geobacillus stearothermophilus KIBGE-IB29

Abstract: Highlightsβ-1,4-d-Xylanohydrolase from Geobacillus stearothermophilus KIBGE-IB29 was purified and characterized.The catalytic properties revealed significant stability over broad pH and temperature range.Native-PAGE and In-gel activity assay were carried out.Various organic solvents and detergents significantly improved the enzyme activity.β-1,4-d-Xylanohydrolase showed excellent storage stability for prospective industrial use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…s tearothermophilus KIBGE-IB29 (pHopt. 6.0; Bibi et al, 2018 ) behaved differently by showing their optimum pH from slightly acidic to neutral range. Besides optimum pH in the alkaline range, the stability of these xylanases at higher pH makes them eligible to withstand the industrial extreme conditions.…”
Section: Biophysical Properties Of Extremophilic Endoxylanasesmentioning
confidence: 99%
See 2 more Smart Citations
“…s tearothermophilus KIBGE-IB29 (pHopt. 6.0; Bibi et al, 2018 ) behaved differently by showing their optimum pH from slightly acidic to neutral range. Besides optimum pH in the alkaline range, the stability of these xylanases at higher pH makes them eligible to withstand the industrial extreme conditions.…”
Section: Biophysical Properties Of Extremophilic Endoxylanasesmentioning
confidence: 99%
“…Bhalla et al (2014Bhalla et al ( , 2015 reported the most promising thermostable endoxylanase from Geobacillus WSUCF1 that showed outstanding stability of 12 days by retaining 50% of total enzymatic activity at 70 • C. The group further claimed that this enzyme is the most thermostable enzyme from any other species of Geobacillus to date. Besides, there are several species/strains of Geobacillus that find their optimum temperature at or below 60 • C such as xylanases of G. thermodenitrificans (Irfan et al, 2018), G. stearothermophilus KIBGE-IB29 (Bibi et al, 2018;Mathew et al, 2018), and Geobacillus strain DUSELR 13 (Bibra et al, 2018). Although Geobacillus are obligate thermophiles (Topt.…”
Section: Thermophilic Endoxylanasesmentioning
confidence: 99%
See 1 more Smart Citation